N’-(Pyridin-3-ylmethylene)benzenesulfonohydrazide: Crystal structure, DFT, Hirshfeld surface and in silico anticancer studies - Ozochukwu, Ifeyinwa Stella; Okpareke, Obinna Chibueze; Izuogu, David Chukwuma; Ibezim, Akachukwu; Ujam, Oguejiofo Theophilus; Asegbeloyin, Jonnie Niyi (European Journal of Chemistry, 2021)
A new Schiff base, N’-(pyridin-3-ylmethylene)benzenesulfonohydrazide, was synthesized and characterized by elemental analysis, IR, Mass, 1H NMR and 13C NMR spectroscopy, and single-crystal X-ray determination. The asymmetric molecule crystallized in the monoclinic crystal system and P2(1)/c space group. Crystal data for C12H11N3O2S: a = 9.7547(4) Å, b = 9.8108(4) Å, c = 13.1130(5) Å, β = 109.038(2)°, V = 1186.29(8) Å3, Z = 4, μ(MoKα) = 0.270 mm-1, Dcalc = 1.463 g/cm3, 13338 reflections measured (5.296° ≤ 2Θ ≤ 55.484°), 2790 unique (Rint = 0.0494, Rsigma = 0.0400) which were used in all calculations. The final R1 was 0.0345 (I > 2σ(I)) and wR2 was 0.0914 (all data). In the crystal structure of the compound C12H11N3O2S, molecules are linked in a continuous chain by intermolecular of N∙∙∙HN=N hydrogen bonds. The pyridine moiety is planar, while the benzenesulfonohydrazide group adopts a gauche conformation about C-S-N angle (105.54°). The Hirshfeld surface analysis and fingerprint plots were used to establish the presence, nature, and percentage contribution of the different intermolecular interactions, including N-H∙∙∙N, C-H∙∙∙O, C-H∙∙∙C, and π∙∙∙π interactions, with the C-H contacts having the most significant contribution. The pairwise interaction energies were calculated at the B3LYP/6-31G(d,p) level of theory, and interaction energy profiles showed that the electrostatic forces had the most significant contribution to the total interaction energies of the different molecular pairs in the crystal. In-silico technique was used to examine the compound as a possible anticancer agent. The molecule demonstrated zero violation of the criteria of Lipinski’s rule of five with a polar surface area of 116.03 Å2. The molecule displayed favorable binding interactions with ten selected validated anticancer protein targets ranging from -9.58 to -11.95 kcal/mol and -2.73 to -5.73 kcal/mol on scoring and rescoring, respectively, with London dG and Affinity dG scoring functions. Two proteins; farnesyl transferase and signaling protein, preferred interactions with the Schiff-base over their co-crystallized inhibitors according to London dG scoring. Analysis of binding poses indicated that the Schiff-base made contact with amino acid residues of the two proteins through the N-H, sulphonyl oxygen, and phenyl groups, and this could be exploited in chemical and structural modification towards activity optimization.